Economic benefit in treatment of unintentional childhood injuries by implementation of child-to-child approach - Bratati Banerjee; Rupsa Banerjee; Puneet Mishra; Gopal Krishna Ingle (Wolters Kluwer Medknow Publications, 2021)
Background: Childhood injury has been recognized as a major threat to child survival and health, as well as economic burden, which includes the cost to government and out-of-pocket expenses (OOPE) to families. Child-To-Child Approach is an innovative technique to reduce childhood injuries and expenses on their treatment. Objectives: To assess economic benefit in the treatment of unintentional childhood injuries, including OOPE by families, by the implementation of the child-To-Child approach. Materials and Methods: The present study is part of a quasi-experimental before-and-after intervention study conducted in the rural area of Delhi for the prevention of childhood injuries through intervention by the child-To-Child approach. Cost of injury treatment, including travel and accommodation expenses, and wage loss were noted. The projected gain in the total cost and out-of-pocket expenditure on injury treatment throughout 20 years of childhood and adolescence were calculated. Results: Both incidences of injuries and total expenditure for treatment of injuries had decreased during the postintervention period in the intervention group, against a rise in the control group. The proportion of OOPE for availing private health care facilities for treatment of injuries, which was more than one-fourth of total expenses, also had decreased in the intervention group during the postintervention period. On economic analysis, it is projected that there will be enormous gain in cost by the implementation of child-To-Child approach in the study area in 20 years, along with saving of OOPE of the families. Conclusion: Child-To-Child approach is effective in preventing childhood injuries and reducing the cost of treatment of injuries.